SAT0127 Gout and RA: not Such A Rare Coexistence after All?. (10th June 2014) - Petsch, C.; Araujo, E.; Englbrecht, M.; Hueber, A.; Lell, M.; Schett, G.; Manger, B.; Rech, J.
Abstract : Background: According to the current rheumatology literature, the simultaneous occurrence of rheumatoid arthritis (RA) and gout is rare and only a few cases have been reported to date.[1] However, clinical practice suggests otherwise. Objectives: To investigate the prevalence of urate deposits in patients with diagnosed RA and hyperuricemia and to identify prognostic factors that could lead to the development of clinical gout in these patients. Methods: 100 patients who fulfilled 2010 ACR/EULAR criteria for RA and had a serum uric acid (SUA) level above 6 mg/dl were included into the study. The presence of monosodium urate (MSU) deposits in joints and tissues was confirmed by means of dual energy computed tomography (DECT), a new imaging tool using x-ray beams of two different energies to differentiate MSU from connective tissues and from calcium containing structures by their absorption properties.[2] Automated volume measurement was used to display the amount of MSU deposition in positive DECT scans. Results: 20% of scans were positive in the whole cohort in contrast to 70% in the seronegative RA subpopulation. Seronegativity was defined as negative rheumatoid factor and anti-CCP antibodies. According to a logistic regression model analysis, seronegative status showed significance for the presence of uric acid deposits (Wald χ 2 =5.280, Exp (B) =0.221, 95% CI=0.061 – 0.801, p=0.022) whereas SUA was not a significant predictor. Mean deposit volume was 130±60 mm 3 . Larger deposits were significantly associated with a higher DAS 28. Conclusions: In contrast to current rheumatology literature suggesting a rare coexistence of rheumatoid arthritis (RA) and gout, we found a considerable number of RA patients with hyperuricemia presenting MSU deposits in typical locations using DECT. Seronegative status is an independent variable related to positive findings and correlation of volume and disease activity might indicate a misdiagnosis of RA in some cases. Polyarticular gout should be considered as an additional and differential diagnosis in patients with RA and hyperuricemia. References: Kuo CF, Tsai WP, Liou LB. Rare copresent rheumatoid arthritis and gout: comparison with pure rheumatoid arthritis and a literature review. Clin Rheumatol 2008;27:231-235. Manger B, Lell M, Wacker J, et al. Detection of periarticular urate deposits with dual energy CT in patients with acute gouty arthritis. Ann Rheum Dis 2012;71:470-472. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2993